Does Corruption Increase or Decrease Employment in Firms? - Beltrán, Arlette (Taylor and Francis, 2015)
This article uses representative data for firms for Latin American firms and show that corruption decreases employment in firms. This result is robust to changes in specification and also consistent with the use of an instrumental variables approach. Corruption appears to negatively impact the growth and wealth in a country, not by introducing labour distortion in firms, but by keeping them small.